2019
DOI: 10.3390/geosciences9030105
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Rules. I. Exoplanet Incidence and Metallicity

Abstract: Discovery of only handful of exoplanets required to establish a correlation between giant planet occurrence and metallicity of their host stars. More than 20 years have already passed from that discovery, however, many questions are still under lively debate: What is the origin of that relation? what is the exact functional form of the giant planet -metallicity relation (in the metal-poor regime)?, does such a relation exist for terrestrial planets? All these question are very important for our understanding o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 296 publications
(476 reference statements)
4
48
0
Order By: Relevance
“…13 of transiting brown dwarfs and low-mass stars. Figure 13 shows the most common metallicity for brown dwarf host stars is at [Fe/H] ∼ 0, which is consistent with previous findings that brown dwarfs are not preferentially found around metal rich stars like hot Jupiters and are more consistent with metallicity distributions of stars without substellar companions or stars with low-mass planets (e.g., Ma & Ge 2014;Mata Sánchez et al 2014;Maldonado et al 2019;Adibekyan 2019). Maldonado & Villaver (2017) found that stars with less massive brown dwarfs tend to have higher metallicities than stars with more massive brown dwarfs, which is consistent with the interpretations of Ma & Ge (2014) and Maldonado et al (2019) that more massive brown dwarfs tend to form more like low-mass stars.…”
Section: -150 M Jup Transiting Companion Radius-mass Relationshipsupporting
confidence: 89%
“…13 of transiting brown dwarfs and low-mass stars. Figure 13 shows the most common metallicity for brown dwarf host stars is at [Fe/H] ∼ 0, which is consistent with previous findings that brown dwarfs are not preferentially found around metal rich stars like hot Jupiters and are more consistent with metallicity distributions of stars without substellar companions or stars with low-mass planets (e.g., Ma & Ge 2014;Mata Sánchez et al 2014;Maldonado et al 2019;Adibekyan 2019). Maldonado & Villaver (2017) found that stars with less massive brown dwarfs tend to have higher metallicities than stars with more massive brown dwarfs, which is consistent with the interpretations of Ma & Ge (2014) and Maldonado et al (2019) that more massive brown dwarfs tend to form more like low-mass stars.…”
Section: -150 M Jup Transiting Companion Radius-mass Relationshipsupporting
confidence: 89%
“…This result has evolved into the now well-known giant planet-metallicity correlation; that is, the higher the metallicity of a star, the more likely it is to host a giant planet (Santos et al 2004;Johnson et al 2010;Maldonado et al 2012;Mortier et al 2013;Schlaufman 2014). This result was recently reviewed by Adibekyan (2019), who reanalysed the giant planet-metallicity correlation using the homogeneous stellar parameters listed in the SWEET-Cat catalogue . They contrasted their sample of FGK dwarf star hosts (with planets discovered by the RV and transit methods) with a comparison sample of FGK stars hosting no planets from the HARPS GTO program (see Adibekyan et al 2012), which has stellar parameters derived using the same method as those in SWEET-Cat (thus making them directly comparable).…”
Section: Introductionmentioning
confidence: 86%
“…Returning to Adibekyan (2019), it is now worth noting that a KS test shows the hosts of their separate radial velocity and transiting planet samples have indistinguishable metallicity distributions, despite the planets having significantly different orbital period regimes. Their transiting sample has an average orbital period of 11 days, whereas the average for their RV sample is 1202 days.…”
Section: Introductionmentioning
confidence: 99%
“…There is no apparent bias with planetary mass, apart from that stars with higher metallicities (here traced by [O/H]) tend to host more massive planets (e.g. Fischer & Valenti 2005;Johnson et al 2010;Adibekyan 2019). The mean rising trend in the plot is a result of the increasing production of carbon at later cosmic times (Sect.…”
Section: C/o In Stars With and Without Confirmed Planet Detectionsmentioning
confidence: 91%